Clinical relevance of reduced decorrelation signals in the diabetic inner choroid on optical coherence tomography angiography - Yoko Dodo (Nature Portfolio, 2017)
Abstract Diabetes induces lesions of the retinal and choroidal capillaries, which promote the pathogenesis of diabetic retinopathy (DR). The decorrelation signals in optical coherence tomography angiography (OCTA) represent the blood flow and vascular structure, and three-dimensional OCTA images enable individual capillary layers to be evaluated separately. The current study documented that en-face OCTA images revealed spots of flow void in the choriocapillaris layer in eyes with DR. Quantitative investigation demonstrated that non-flow areas within the central subfield (CSF) increased in eyes with more severe DR grades. The non-flow areas in the choriocapillaris layer were also associated with poorer visual acuity (VA) in all 108 eyes. A modest correlation was noted between the areas of flow void and poorer VA in 69 eyes without DME, whereas the non-flow areas were not related to VA or to CSF thickness measured by OCT in 39 eyes with DME. In 12 eyes with ischemic maculopathy, the choriocapillaris layer beneath the disrupted ellipsoid zone of the photoreceptor (EZ) had greater areas of flow void than did the area beneath an intact EZ. These data suggested that disrupted choroidal circulation has clinical relevance and contributes to the pathogenesis of DR.